A Study on the Inheritance Status and Enhancement Path of Chinese Ancient Poetry Art Songs Integrated into Vocal Music Teaching in Contemporary Colleges and Universities - Zhao, Xin (Pacific International Journal, 2023)
Traditional culture with refined and meaningful words, beautiful verses and rich connotations. As a product of the fusion of East and West, Chinese ancient poetry art songs is a perfect fusion of the profound Chinese poems and Western elegant music creation techniques, which is the continuous development of the excellent traditional Chinese culture. Colleges and universities, as the main channel for the training of high-quality music talents, shoulder the important responsibilities of talent training, cultural inheritance and scientific research. Since the birth of Chinese ancient poetry art songs, there have been high requirements in vocal singing, mood shaping and cultural expression, etc. Therefore, integrating Chinese ancient poetry art songs into vocal teaching in colleges and universities can not only improve the students’ vocal singing level and comprehensive cultural literacy, but also enhance the students’ cultural self-confidence in learning and singing. However, it is found that the inheritance status of Chinese ancient poetry art songs integrated into vocal music teaching in colleges and universities is not optimistic, and there are problems such as insufficient attention of students, irrational curriculum facilities, lack of attention to the improvement of comprehensive quality, confusing use of teaching materials, and fewer opportunities for students to practise, and so on. Through the analysis of the causes, it is found that there are misunderstandings in the students’ cognition, the teaching objectives are not clear enough, the teaching faculty is scarce, and the teaching ability needs to be improved. In view of the above problems, this study proposes that students should be guided to improve their value cognition and set up a correct sense of inheritance; teachers should clarify the teaching objectives and create a reasonable curriculum system; institutions should strengthen the training of teachers and enhance the ability of diversified teaching; institutions should encourage teachers to reasonably prepare teaching materials and provide a scientific teaching basis; and institutions and teachers should also actively develop practical activities and provide sufficient opportunities for exercise.